Antimicrobial and antioxidant AIE chitosan-based films incorporating a Pickering emulsion of lemon myrtle (Backhousia citriodora) essential oil. (December 2022) - Liu, Lingdai; Swift, Simon; Tollemache, Cherie; Perera, Janesha; Kilmartin, Paul A.
Abstract: Films based on chitosan (CS) and Lemon Myrtle ( Backhousia citriodora ) essential oil (LEO) were prepared that exhibited novel dose-dependent fluorescent patterns owing to aggregation-induced emission (AIE) effects. Specifically, chitosan-coated alkali lignin (CS@AL) colloid particles were obtained by a facile one-pot ultrasonication, and were used to prepare LEO-loaded Pickering emulsions (CS@ALPE). Different amounts of CS@ALPE were incorporated into CS-based film-forming solutions. The composite (CS@ALPE-CS) films contained LEO/CS (w/w) ratios around 0%, 5.9%, 14.8%, 29.6% and 59.2% after solution casting. The microstructures, optical properties, water affinity, mechanical attributes, fluorescent characteristics, as well as antimicrobial and antioxidant efficacies of CS@ALPE-CS films were assessed for multifunctional food packaging. 0.5% (w/v) of CS@AL particles (pH ∼4.3 to 4.6) enabled stabilization of CS@ALPE (φ = 0.4) for at least 35 days. Adding CS@ALPE with appropriate LEO/CS (w/w) ratios modified the properties of the composite films. The 0.5CS@ALPE-CS film (with LEO/CS (w/w) around 29.6%) was the most promising candidate for multifunctional packaging considering its optimal optical properties, resistance to moisture and mechanical stress, characteristic fluorescent attributes along with antimicrobial and antioxidant activities. Graphical abstract: A schematic illustration of a dose-dependent AIE fluorescence pattern correlating to the relative contents of CS@ALPE to CS within CS@ALPE-CS films. Image 1 Highlights: Emulsions of lemon myrtle essential oil stabilized by chitosan-coated lignin. Facile one-pot scheme for chitosan-based films incorporating the essential oil. Films with improved UV-shielding, antimicrobial and antioxidant properties. Reactions between chitosan and essential oil yielded Schiff base products. Correlations between fluorescence emission spectra and essential oil content.